Acciones de prevención de apiñamientos dentales según tipos de dentición - Tania Maribel, Chaglla Moyolema (2021)
ABSTRACT Dental crowding is prevalent among patients who come for consultation either for esthetic, masticatory, or oral hygiene reasons. This literature review was carried out to establish the actions for preventing dental crowding in each type of dentition according to the factors that can cause it. The method applied was the bibliographic search in databases such as PubMed, Google Scholar, Science Direct, and Worldwide Science; through the application of inclusion and exclusion criteria, considering the average citation count and the impact factor of the journals in which the articles were published, obtaining a final number of 60 publications for the study process. The actions to prevent the appearance and progression of dental crowding are: in the deciduous dentition, breastfeeding, and reduction of the use of bottles; in the mixed dentition, the preservation of teeth and interproximal contact points, the use of space maintainers in the case of premature tooth loss, early treatment of onychophagia and bruxism, analysis of mixed dentition; and in the permanent dentition: the correct use of orthodontic procedures, including fibrotomy, interproximal reduction, post-orthodontic retention and extraction of poorly angled third molars. Recurrence in the treatments is explained by the combination of failures in the corrective procedures. These external factors alter the results and the bone, muscular and dental changes typical of aging. Keywords: dental crowding, orthodontics, oral health prevention. Reviewed by: Dr. Narcisa Fuertes, PhD. ENGLISH PROFESSOR Cc: 1002091161